One nation, one beer: The mythology of the new South Africa in advertising - Britten, Sarah Jane (My University, 2006)
The New South Africa came into being on February 2, 1990, with State President F.W. de Klerk’s announcement of the sweeping changes that signalled the end of white minority rule. The New South Africa immediately assumed mythical status, functioning as a structuring, legitimating narrative in the face of a history that carried with it the possibility of inter-racial conflagration. Later, another myth emerged, that of the rainbow nation, together with a latter day epic hero in the form of Nelson Mandela. Together with a third, less defined myth of the freedoms promised by the new Constitution of 1996, these constitute a mythology of the New South Africa. Advertising played an important role in the propagation and interrogation of these myths. Campaigns for an assortment of consumer goods and services tracked momentous shifts in society, politics and culture, often with penetrating insight and incisive humour. Three campaigns, for Castle Lager (beer), Vodacom (cellular network) and Castrol (motor oil), and individual advertisements for Nando’s (fast food chicken), Sales House (retail clothing) and South African Airways, are analysed. The material is approached using a hybrid methodology of a structure that draws upon Fairclough’s (1989, 1995) Critical Discourse Analysis, while analysing the texts themselves using an approach most closely allied to the social semiotics of Barthes (1972). Using this approach, it can be seen, for example, how the Castle Lager ‘Friendship’ campaign is perhaps the most sustained articulation of the ideals embodied in the New South Africa and particularly the myth of the rainbow nation. In contrast, an analysis of the Vodacom ‘Yebo Gogo’ campaign reveals that even at its most dominant, the mythology of the New South Africa was being undermined by prototypical myths that would consolidate under the heading of the African renaissance. An overview of all of the campaigns analysed in this thesis point to the existence of three types of approach to advertising the nation, namely, incantatory, novelistic and identificatory. Incantatory advertising reproduces dominant national myths without questioning them; in contrast, novelistic advertising interrogates the assumptions upon which such myths are based even if it ultimately endorses them. Identificatory advertising focuses on ‘typical’ examples of what constitutes South Africanness, without any attached overt ideological agenda. Incantatory advertising tends to emerge at important national anniversaries or international sporting events, while identificatory advertising became more prominent as the mythology of the New South Africa became less immediate. It is likely that advertising will continue to play a significant role in the imagining of the South African nation.
Faculty of Humanities 9301506x Sarah-Britten@za.yr.com
Keywords: South Africa; State; freedoms; mythology; inter-racial